Determination of Nutritional and Biochemical Composition of Selected Pleurotus spps. (14th January 2023) - Irshad, Asma; Tahir, Aisha; Sharif, Sumaira; Khalid, Aisha; Ali, Sajed; Naz, Alisha; Sadia, Haleema; Ameen, Ayesha
Abstract : The global demand for good quality food is going to be increased gradually. Mushrooms are broadly used as healthy nutritious meals. The nutritional values of extracts from four distinct Pleurotus species— Pleurotus ostreatus, Pleurotus sajor-caju, Pleurotus sapidus, and Pleurotus columbinus —were determined in the current study. Firstly, proximate analysis of selected Pleurotus species was performed followed by the Bradford assay to analyze the protein spectrophotometrically; high-performance liquid chromatography (HPLC) was performed for sugar determination while GC-MS was done to determine fatty acids on organic extracts of selected mushrooms. Descriptive statistics were used to calculate the percentages while significance was determined by SPSS statistics. The results depicted that fat, protein, ash, fiber, energy contents, and total carbohydrate were in the range of 0.64-2.02%, 16.07-25.15%, 2.1-9.14%, 6.21-54.12%, 342.20-394.30 kcal/100 g, and 65.66-82.47%, respectively. The protein's maximum concentration was observed in P. ostreatus followed by P. columbinus>P. sajor-caju>P. sapidus, sequentially. Various sugars may or may not be present in selected Pleurotus spps. Among the fatty acids, the prevalence of UFA was more than that of saturated fatty acids among all selected mushrooms. From this study, it is concluded that all four Pleurotus spps. have excellent nutritional composition and can be used as valuable food and a great source of biochemical compounds.